An exploratory investigation of entrepreneurial space: the case of small sawmills, North Karelia, Finland. - Selby, J. Ashley (The Society of Forestry in Finland - The Finnish Forest Research Institute, 2009)
A theoretical and philosophical examination of the ways in which behaviour of entrepreneurs relates to the business environment, with an empirical case study of the business attitudes, perceived business environments and ability to use business-related information of small sawmill entrepreneurs.